Experience in stabilisation of rock slopes in Pahang / Muhammad Hafeez Osman … [et al.] - Osman, Muhammad Hafeez (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2009)
Two cases regarding the histories of rock slopes repair and stabilisation of unstable boulder along Bukit Cincin to Genting Highlands and along the road from Gap to Fraser Hill in Pahang are presented. On 30th October 1997, 10 locations of road failure occurred along the road from Bukit Cincin to Genting Highland and in December 1997, 33 locations of slope failures occurred along the road from Gap to Eraser Hill during the monsoon seasons. Loose and fractured rocks were removed and covered with polyvinyl chloride (PVC) coated anchored wire netting to prevent rocks fall while rock buttress was used to stabilise unstable boulders in soil slope. The repair works at Location 5 along the road from Bukit Cincin to Genting Highland where highly fractured rock slope and unstable boulder in soil slope occurred and the repair works at Location 10 along the road from Gap to Eraser Hill where highly fractured rock slope occurred are fully discussed in this paper.